Answer:
(-2, 6)
Step-by-step explanation:
Equation of a circle is:
(x − h)² + (y − k)² = r²
where (h, k) is the center and r is the radius.
In this case, the center is (-2, 6).
Answer:
13
Step-by-step explanation:
Not sure, i'm sorry
should be the same logic as
a=b
b=c
a=c
Answer:
2
Step-by-step explanation:
because for every 3 teaspoons of salt he will have 1 tablespoon of salt and 6 divided by 3 is 2
Answer:
6.5
Step-by-step explanation:
I hope you have a great day!!
It’s missing axis labels
Hope this helps!